Assessing Landslide Susceptibility Using Analytical Hierarchy Process (AHP) and Frequency Ratio (FR) in the Oued Lebene Watershed, North Morocco - El Amarty, Fahed; Chakir, Afaf; Benaabidate, Lahcen; Lahrach, Abderrahim (Iraqi Journal of Science, 2025)
Assessing landslide susceptibility is paramount in planning, implementing management plans, and mitigating risks in areas vulnerable to this hazard. The present study, based on the Analytical Hierarchy Process (AHP) and Frequency Ratio (FR) in conjunction with Geographic Information Systems (GIS), aims to evaluate landslide susceptibility in the Oued Lebene watershed. Eleven causal factors determining landslides were considered, including elevation, slope, aspect, curvature, relative relief, lithology, precipitation, and distance to drainage, distance to road, NDVI, land use, and vegetation cover. By applying AHP and FR methods, a correlation between previous landslides and triggering factors was established to assess their influence on landslide susceptibility. Maps depicting sensitivity were produced using each method, categorized into four groups, and subsequently validated using the area under the curve (AUC). The AHP approach unveiled that regions characterized by very high, high, moderate, and low susceptibility correspondingly constitute 0.36%, 21.24%, 70.57%, and 7.84% of the total area. Likewise, the FR technique suggests that regions with very high, high, moderate, and low susceptibility make up 0.08%, 2.50%, 39.39%, and 58.03% of the study area, respectively. The findings indicate that FR, with an AUC of 0.722, outperformed AHP, which achieved an AUC of 0.711, in delineating the study areas concerning historical landslides. These maps will be of valuable utility for planners and decision-makers for meticulous planning and risk mitigation purposes.